Supply chain management strategy, planning, and operation - Chopra, Sunil; Meindl, Peter (Pearson Education, 2013)
This book outlines the main concepts so that students may understand what creates a competitive advantage. This text also provides strong coverage of analytic skills so students can gauge the effectiveness of the techniques described in the text.